Intracath in neonates- does size matter? - Rathod, Kamleshkumar G.; Deo, Ruta M. (International Journal of Contemporary Pediatrics, 2020)
Background: Intravenous cannulation, though a first line procedure is very challenging in new-born patients. Improving its longevity will prevent frequent resisting and complications and help the baby and doctor immensely. this study analyses parameters that are likely to affect the longevity of intravenous cannula on same. This study analyses the parameters likely to affect the longevity of intravenous cannulas and effect of gauge on the same. The objectives considered are to determine the ideal gauge of cannula for peripheral vein catheterization, evaluate the complications necessitating its removal and to find the best possible peripheral vein for such cannulation; if any. Methods: This is a hospital based prospective observational study in 500 intravenous cannulas studied from point of insertion to removal. Results were tabulated and analysed based on Chi-square test and Kaplan Meir slopes were plotted. Main outcome measure- effect of cannula site on its in-situ life. Results: Term infants showed increased life span as gauge size increased (maximum with 20 G). Pre-terms had best longevity with 22 gauge. Most common cause warranting removal of cannulas were local swelling and erythema. Prick site complications leading to serious morbidity occurred in <5%. Conclusion: Gauge 22 is best suited for iv access in neonates. Gestational age and site of cannulation are strong determinants of gauge size and longevity. Intravenous cannulas in neonatal intensive care unit (NICU) should be selected considering factors for maximum lifespan of the catheter.